1973
DOI: 10.1113/jphysiol.1973.sp010188
|View full text |Cite
|
Sign up to set email alerts
|

Differential release of acetylcholine from the hypothalamus and mesencephalon of the monkey during thermoregulation

Abstract: SUMMARY1. In unanaesthetized monkeys acclimated to primate chairs, 101 isolated sites in the hypothalamus and mesencephalon were perfused at a rate of 30-50,sl./min by means of push-pull cannulae. The perfusate, which contained an anticholinesterase, was assayed for acetylcholine (ACh) activity on the guinea-pig ileum in the presence of neostigmine.2. The body temperature of each animal was monitored continuously during an experiment by colonic and brain thermistors. To alter the ambient temperature by 15-20' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…A similar study in the rhesus monkey (Myers and Beleslin, 1971), where serotonin levels were monitored found that cooling evoked an increased release of serotonin whereas heating either did not affect or inhibited serotonin release. Similar results were found for acetylcholine levels in another study on the rhesus monkey (Myers and Waller, 1973). To conclude, an overview will be given of the evidence in support of a physiological role for dopamine in thermoregulation:…”
supporting
confidence: 62%
“…A similar study in the rhesus monkey (Myers and Beleslin, 1971), where serotonin levels were monitored found that cooling evoked an increased release of serotonin whereas heating either did not affect or inhibited serotonin release. Similar results were found for acetylcholine levels in another study on the rhesus monkey (Myers and Waller, 1973). To conclude, an overview will be given of the evidence in support of a physiological role for dopamine in thermoregulation:…”
supporting
confidence: 62%
“…These authors also suggested that NA inhibits the cholinergic heat production pathway but does not activate a heat-loss pathway which they concluded apparently does not exist within the AH/POA. They obtained evidence for a cholinergic heat-loss pathway in the cat and monkey but only within the posterior hypothalamus (Myers & Yaksh, 1969;Myers & Waller, 1973, 1975 (Myers & Chinn, 1973) provide a basis for the suggestion that NA may activate heat loss pathways directly.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggests that this model requires modification and we propose that NA be given an additional role as acting in an excitatory manner within a heat loss pathway in the AH/POA. Such noradrenergic neurones may project to a cholinergic heat loss pathway which has been identified within the posterior hypothalamus (Myers & Yaksh, 1969;Myers & Waller, 1973, 1975.…”
mentioning
confidence: 99%
“…It has been postulated that 5-HT acts peripherally resulting in changes in cardiovascular and/or respiratory function or may act by depressing general activity (Myers and Waller, 1977). …”
Section: B Detection Of Rf Heating In Micementioning
confidence: 99%